Agrobacterium‐Mediated Transformation of Setaria viridis, a Model System for Cereals and Bioenergy Crops. Issue 5 (17th May 2021) - Finley, Todd; Chappell, Hal; Veena, Veena
Abstract: Setaria viridis is an emerging model system for the genetic and molecular characterization of cereals and bioenergy crops. Here, we describe a detailed procedure for genetic transformation of the S. viridis accession line ME034V‐1. This method utilizes callus generated from mature seeds for infection with Agrobacterium tumefaciens strain AGL1 to regenerate hygromycin‐resistant stable transgenic plants. It takes approximately 7 weeks to generate callus from mature seeds, 11‐17 weeks from infection to the regeneration of transgenic lines, and an additional 3‐4 weeks for plant growth in the greenhouse for seed collection. The protocol as presented consistently results in transformation frequency of approximately 25% for the generation of transgenic plants, with fewer escapes and higher survivability in soil for optimal seed collection. © 2021 Donald Danforth Plant Science Center. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Generation of S. viridis (Accession ME034V‐1) callus from mature seeds Basic Protocol 2 : Agrobacterium ‐mediated transformation of callus to generate transgenic plants Basic Protocol 3 : Plantlet transplantation in soil, plant growth in greenhouse, and seed collection Support Protocol : Preparation of Agrobacterium culture for infection